SANKSI HUKUM TERHADAP PELANGGARAN KODE ETIK ANGGOTA POLISI YANG MELOLOSKAN TAHANAN - Maidianti, Silfy; Liza Nofianti (Justici, 2024)
Abstract In several cases of violations, it was not only the general public who became perpetrators but also members of the Police who were involved in violations. Violations committed by members of the Police are included in violations of the Disciplinary Regulations and the Professional Code of Ethics for the Indonesian National Police. In fact, in the field there are still many violations committed by members of the National Police, this has had an impact on the creation of negative public opinion and the emergence of a bad image and antipathy from the community, so that the implementation of tasks in the field cannot be carried out optimally due to lack of support and a sense of public distrust of the Police. One of the acts of abuse of authority by the police is to release prisoners. This research is a doctrinal legal research that not only takes inventory of primary materials in the form of legislation, then organizes them into a collection that facilitates retrieval, but also collects secondary legal materials. The data analysis method used is descriptive analysis. The conclusion obtained is, if the police deliberately release detainees without a valid reason in carrying out their duties, they can be subject to criminal sanctions as stipulated in Article 426 of the Criminal Code.